Epithelial apical glycosylation changes associated with thin endometrium in women with infertility - a pilot observational study - Marina M. Ziganshina; Nataliya V. Dolgushina; Galina V. Kulikova; Nafisa M. Fayzullina; Ekaterina L. Yarotskaya; Nailia R. Khasbiullina; Nigora F. Abdurakhmanova; Aleksandra V. Asaturova; Alexander I. Shchegolev; Alina A. Dovgan; Gennady T. Sukhikh (BMC, 2021)
Abstract Background Low endometrial receptivity is one of the major factors affecting successful implantation in assisted reproductive technologies (ART). Infertile patients with thin endometrium have a significantly lower cumulative clinical pregnancy rate than patients with normal endometrium. Molecular pathophysiology of low receptivity of thin endometrium remains understudied. We have investigated composition of glycocalyx of the apical surface of luminal and glandular epithelial cells in thin endometrium of infertile women. Methods Thirty-two patients with tubal-peritoneal infertility undergoing in vitro fertilization (IVF) were included in the study. Endometrial samples were obtained in a natural menstrual cycle. Patients were divided into two groups: patients with normal endometrium (≥8 mm) and with thin endometrium (< 8 mm). Histochemical and immunohistochemical analysis of paraffin-embedded endometrial samples was performed using six biotinylated lectins (UEA-I, MAL-II, SNA, VVL, ECL, Con A) and anti-LeY and MECA-79 monoclonal antibodies (MAbs). Results Complex glycans analysis taking into account the adjusted specificity of glycan-binding MAbs revealed 1.3 times less expression of MECA-79 glycans on the apical surface of the luminal epithelial cells of thin endometrium compared to normal endometrium; this deficiency may adversely affect implantation, since MECA-79 glycans are a ligand of L-selectin and mediate intercellular interactions. The glycans containing a type-2 unit Galβ1-4GlcNAcβ (LacNAc) but lacking sulfo-residues at 6-OH of GlcNAcβ, and binding to MECA-79 MAbs were found; they can be considered as potential markers of endometrium receptivity. Expression of the lectins-stained glycans on the apical surfaces of the luminal and glandular epithelial cells did not differ significantly. Correlation between the expression of difucosylated oligosaccharide LeY on the apical surfaces of the luminal and glandular epithelial cells was found in patients with thin endometrium and recurrent implantation failure. A similar relationship was shown for mannose-rich glycans. Conclusions Specific features of key glycans expression in epithelial compartments of thin endometrium may be essential for morphogenesis of the endometrial functional layer and explain its low receptivity.